KETAHANAN MASYARAKAT DALAM BERMUKIM PADA KAWASAN RAWAN BANJIR ROB DI DESA PANTAI BAHAGIA KABUPATEN BEKASI - Pradhana, Ivan Rahmadi; Pontoh, Nia Kurniasih; Harahap, Tetty (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Tidal floods are floods caused by sea water, usually hitting areas around the coast (PKK RI, 2021). In the last 20 years, the northern coastal area of ​​Bekasi Regency floods caused by rising sea levels. Based on geographical location, there have been floods in the last 20 years (2001-2022) which occurred in the middle of the month every year. This study aims to identify the factors that influence the resilience of the community in facing tidal flood conditions in Pantai Bahagia Village. The data collection method used in this study used simple and stratified random sampling and observation. The data analysis method used was descriptive qualitative, descriptive statistics and cross-tabulation associations. Based on the results of the analysis, the community already has the ability to adapt to flooding but has not yet reached the transformation stage, namely the level of resilience to save the community from tidal floods. As for the community residential areas that are inhabited, they cannot be converted as settlements because they are still fully owned by state-owned company. The community prefers to survive with several indications of resilience as an adaptation to tidal floods.